If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln(x) + 2x = 0 Multiply nL * x nxL + 2x = 0 Solving nxL + 2x = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2x' to each side of the equation. nxL + 2x + -2x = 0 + -2x Combine like terms: 2x + -2x = 0 nxL + 0 = 0 + -2x nxL = 0 + -2x Remove the zero: nxL = -2x Divide each side by 'xL'. n = -2L-1 Simplifying n = -2L-1
| 2x+4(x-6)=3(x+2) | | -3(2y+5)+4(3y-6)= | | -8+7+4x=69 | | 7m-25=2n | | 3x^6-24x^3=0 | | 7x-42=2x+38 | | 2z-7z=-z-1-9z | | 4x+9+x=-6 | | 8m-4=8m | | -15x-15=90 | | X-2.16=9.87 | | 12x-12=4+6x | | 3/x=9/25 | | X-9.7=7.8 | | 29,000,000/X=8.57 | | 9z+6z=7z-6+3z | | -3(4t+5)+7(3t-4)= | | -6(3x-4)=120 | | t−8=5(t/3−8 | | 86=x+6x+9 | | 18x+6=2x-9x | | 9x/5-33=3 | | 73=4x+5x+10 | | 6a+18=0 | | x+124=431 | | 0.2(d-2)=0.3d+5-3+0.1d | | 3(x+4)+4(7x-3)= | | 6x+2=2x-7x | | 9p=6p+22 | | (6-2x)+2=10 | | 4y+3=31 | | t−8=5(t/3−8) |